2023
DOI: 10.5811/westjem.2022.12.57098
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Physician Observations and Attitudes on Law Enforcement Activities in the Emergency Department

Abstract: Introduction: Law enforcement officers (LEO) interact with patients and clinicians in the emergency department (ED) for many reasons. There is no current consensus on what should comprise, or how to best enact, guidelines that ideally balance LEO activities in the service of public safety with patient health, autonomy, and privacy. The purpose of this study was to explore how a national sample of emergency physicians (EP) perceives activities of LEOs during the delivery of emergency medical care. Methods: Mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This corresponds with the results of a recent survey of emergency medicine physicians, who prioritized staff and public safety most highly in navigating these interactions. 16 This indicates then when clinicians think about LEO presence, they may be focused on issues outside of the core patient-centered mission of healthcare. Consistent with patient perspectives in previous research, 8 9 11 many respondents found LEOs' presence a detriment, by disrupting clinical care, causing emotional distress to patients, or leading patients to minimize symptoms or withhold medically pertinent information that could pose legal risks.…”
Section: Open Accessmentioning
confidence: 99%
“…This corresponds with the results of a recent survey of emergency medicine physicians, who prioritized staff and public safety most highly in navigating these interactions. 16 This indicates then when clinicians think about LEO presence, they may be focused on issues outside of the core patient-centered mission of healthcare. Consistent with patient perspectives in previous research, 8 9 11 many respondents found LEOs' presence a detriment, by disrupting clinical care, causing emotional distress to patients, or leading patients to minimize symptoms or withhold medically pertinent information that could pose legal risks.…”
Section: Open Accessmentioning
confidence: 99%
“…Thus, police presence may impact on access to relevant care structures such as staffing and delay time-sensitive ED processes. Recent evidence has identified that the conflicting priorities between police and ED clinicians may lead to compromised clinical care (Khatri et al, 2023), which can then impact on patient outcomes. Additionally, patients who have an involuntary assessment order (compared to those without an involuntary assessment order) are more likely to encounter outcomes such as a prolonged ED stay (Trivedi et al, 2019;Wardrop et al, 2022a).…”
Section: Backg Rou N Dmentioning
confidence: 99%